High-resolution resonant inelastic x-ray scattering study of the electron-phonon coupling in honeycomb alpha-Li2IrO3 - Vale, JG; Dashwood, CD; Paris, E; Veiga, LSI; Garcia-Fernandez, M; Nag, A; Walters, A; Zhou, K-J; Pietsch, I-M; Jesche, A; Gegenwart, P; Coldea, R; et al. (American Physical Society, 2019)
The excitations in honeycomb α-Li2IrO3 have been investigated with high-resolution resonant inelastic X-ray scattering (RIXS) at the O K edge. The low-energy response is dominated by a fully resolved ladder of excitations, which we interpret as being due to multiphonon processes in the presence of strong electron-phonon coupling (EPC). At higher energies, the orbital excitations are shown to be dressed by phonons. The high quality of the data permits a quantitative test of the analytical model for the RIXS cross section, which has been proposed to describe EPC in transition-metal oxides (TMOs). We find that the magnitude of the EPC is comparable to that found for a range of 3d TMOs. This indicates that EPC may be of equal importance in determining the phenomenology displayed by corresponding 5d-based systems.